2022
DOI: 10.3390/v15010038
|View full text |Cite
|
Sign up to set email alerts
|

Clade 2.3.4.4b H5N8 Subtype Avian Influenza Viruses Were Identified from the Common Crane Wintering in Yunnan Province, China

Abstract: The seasonal migration of wild aquatic birds plays a critical role in the maintenance, transmission, and incursion of the avian influenza virus (AIV). AIV surveillance was performed during 2020–2021 in two national nature reserves with abundant wild bird resources in Yunnan, China. Four H5N8 AIVs isolates from the common crane were identified by next-generation sequencing. Phylogenetic analysis demonstrated that all eight gene segments of these H5N8 AIVs belonged to clade 2.3.4.4b high-pathogenic AIV (HPAIV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Actively monitoring the prevalence and evolution of influenza viruses will contribute to the development of prevention and control measures against the influenza epidemic. In this study, 11 isolates of H9N2 were identified in our annual surveillance for AIV in Dashanbao Black-Necked Crane National Nature Reserve and Huize Black-Necked Crane National Reserve, in Yunnan Province, China, from the fecal samples of wild birds and surrounding domestic poultry during 2021-2022 (Yang et al, 2022). The viral phylogenetic analysis revealed distinct genotypes between strains obtained from wild birds and domestic birds.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Actively monitoring the prevalence and evolution of influenza viruses will contribute to the development of prevention and control measures against the influenza epidemic. In this study, 11 isolates of H9N2 were identified in our annual surveillance for AIV in Dashanbao Black-Necked Crane National Nature Reserve and Huize Black-Necked Crane National Reserve, in Yunnan Province, China, from the fecal samples of wild birds and surrounding domestic poultry during 2021-2022 (Yang et al, 2022). The viral phylogenetic analysis revealed distinct genotypes between strains obtained from wild birds and domestic birds.…”
Section: Introductionmentioning
confidence: 89%
“…In this study, 11 H9N2 AIV isolates were analyzed, including four from common crane (Grus grus), two from bar-headed goose (Anser indicus) and five from domestic poultry (Gallus gallus). These isolates had been previously identified during our AIV surveillance at the Dashanbao Black-Necked Crane National Nature Reserve and the Huize Black-Necked Crane National Reserve, in Yunnan Province, China (Yang et al, 2022). The identification procedures for the H9N2 AIV isolates were as follows: initially, fresh samples were propagated in chicken embryos, and the allantoic fluid was tested using the hemagglutination assay.…”
Section: Materials and Methods H N Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 814 fecal samples were collected from wading birds in the natural reserves in Yunnan Province, China. Detailed information regarding sample collection was given in a previous study [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Considering the prevalence of FAdVs in domestic poultry in China, and their potential for cross-species transmission, we conducted a surveillance of FAdVs in wild birds as part of a comprehensive virus surveillance program on wildfowls in Yunnan Province, China, initiated by the local administrative department of wildlife conservation [ 10 ]. Specifically, a strain of FAdV-4 was successfully isolated from a fecal sample of black-necked crane ( Grus nigricollis ).…”
Section: Introductionmentioning
confidence: 99%